2020
DOI: 10.1038/s41598-020-76123-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of combination therapy using implantable anticancer drug delivery with thermal ablation in solid tumor

Abstract: Local implantable drug delivery system (IDDS) can be used as an effective adjunctive therapy for solid tumor following thermal ablation for destroying the residual cancer cells and preventing the tumor recurrence. In this paper, we develop comprehensive mathematical pharmacokinetic/pharmacodynamic (PK/PD) models for combination therapy using implantable drug delivery system following thermal ablation inside solid tumors with the help of molecular communication paradigm. In this model, doxorubicin (DOX)-loaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…The mean spatial value of tumor IFP for the networks 1–6 is 1525.7 Pa, 1585.5 Pa, 1698.3 Pa, 1570.2 Pa, 1700.7 Pa and 1868.2 Pa, respectively. The results are good compatible with the numerical studies of Soltani et al 61 , Souri et al 62 , Al-Zu’bi and Mohan 63 as well as the experimental study of Butcher et al 64 , which demonstrated the range of 586–4200 Pa for IFP in the tumor. Moreover, the IFP value in normal tissue is around 53.7–97.5 Pa, that agrees with the values of the experimental study 65 , 66 , which demonstrated the range of − 400 to 800 Pa for IFP in normal tissue.…”
Section: Resultssupporting
confidence: 89%
“…The mean spatial value of tumor IFP for the networks 1–6 is 1525.7 Pa, 1585.5 Pa, 1698.3 Pa, 1570.2 Pa, 1700.7 Pa and 1868.2 Pa, respectively. The results are good compatible with the numerical studies of Soltani et al 61 , Souri et al 62 , Al-Zu’bi and Mohan 63 as well as the experimental study of Butcher et al 64 , which demonstrated the range of 586–4200 Pa for IFP in the tumor. Moreover, the IFP value in normal tissue is around 53.7–97.5 Pa, that agrees with the values of the experimental study 65 , 66 , which demonstrated the range of − 400 to 800 Pa for IFP in normal tissue.…”
Section: Resultssupporting
confidence: 89%
“…The momentum and continuity equations in biological tissue as porous medium, assuming the existence of the source and sink terms, are as follows 32 , 33 : where v i is interstitial fluid velocity, P i is IFP, is the tissue hydraulic conductivity, is the exchange rate of fluid flow from the capillaries to the interstitium, and is the exchange rate from interstitium to the lymph system. These two terms are obtained by the following equations 32 , 33 : where S / V represents the surface area per volume of the microvessels, is the lymph filtration coefficient, and P L is the hydrostatic pressure of lymph.…”
Section: Methodsmentioning
confidence: 99%
“…The cell-death rate depends on the local drug concentration 32 . Drugs unable to efficiently penetrate the tissue are not capable of clearing regions far from the vascular network although they can kill cells in a culture 33 . Additionally, the characteristics of a drug—diffusivity, associating rate, and systemic clearance rate—determine its capability to penetrate solid tumors 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite MRgFUS showing promising pain-control ability, the use of thermal ablation against solid tumors and bone metastatic lesions remains controversial. The main concern associated with thermal ablation is the paucity of evidence regarding local recurrence, and wound healing leads to improvements in the residual tumor after the thermal ablation [ 35 , 36 ]. The long-term local control of thermal ablation involves the modulation of the immune microenvironment into an antitumor environment by combining anticancer drugs with tumor ablation.…”
Section: Discussionmentioning
confidence: 99%